EFFECT OF SUPERVISION AND TIME PRESSURE TO QUALITY OF AUDITOR WORK - Mutimmah Rustianawati; Alwan Sri Kustono; Siti Maria Wardayati (Universitas Pendidikan Ganesha, 2017)
This study aims to determine the effect of Supervision and Time Pressure on the quality of the Auditor's work. This research is a quantitative research. The sampling technique used is asaturated sample. The sample in this study is the auditor of Inspectorate of East Java Province.The data used is primary data with survey method by distributing questionnaires to respondents.Test data is done by testing the validity, testing and reliability test using classical assumption of classical normality, multicollinearity test and heteroskedasitas test. Hypothesis test using multiple regression analysis using SPSS 17.0 The results of this study significantly influence both partially and simultaneously to the quality of the work of auditors.Keywords: Quality of Auditor's Work, Supervision, Time Pressure